THE INVESTIGATION OF CRIMINAL NEGLIGENCE AGAINST VICTIMS OF KANJURUHAN TRAGEDY - Rosmaya, Ina; Tjahjadi, Mochammad Rafly (IUS POSITUM: Journal of Law Theory and Law Enforcement, 2023)
The Criminal Code does not formally define the meaning of negligence or forgetfulness. Then, the definition of negligence must be obtained from the opinions of criminal law experts and serve as a basis for defining the negligence itself. However, the Criminal Code stipulated the negligence in Article 359 and Article 360 of Criminal Code that distinguishes the result of negligence itself. Article 359 of Criminal Code explains the negligence that causes human mortality, and Article 360 of Criminal Code explains the negligence that causes serious injury to the victims. This research aims to determine the causes of Kanjuruhan Malang tragedy, who should be responsible for it, and the efforts to prevent the recurrence of the tragedy itself.  This research is an empirical approach to the problem in accordance with the law that lives in society, as well as collected legal materials that are analyzed using qualitative methods, that produces descriptive information analysis. The results of this research indicate that organizing committee and the security have been negligent by making some mistakes that cause a lot of material and immaterial losses for the supporters. The organizing committee has neglected by not regulating the safety and security of the match according to PSSI regulations. Moreover, Security Officer Steward is negligent by not preparing a risk assessment document according to PSSI Regulations.